1972
DOI: 10.1099/00221287-70-1-87
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Bactoprenol in the Mesosome and Plasma Membranes of Lactobacillus casei and Lactobacillus plantarum

Abstract: SUMMARYAbout one-third of the Cs5 isoprenoid alcohol, bactoprenol, in Lactobacillus casei and L. plantarum cells was in the mesosomes and two-thirds in the plasma membrane. After removal of bound lysozyme from the plasma membrane, the concentration of bactoprenol per mg protein was the same in the mesosomes and in the plasma membrane. Pulse-labelling experiments and chasing with unlabelled precursor showed that bactoprenol is synthesized in both the plasma and mesosome membranes and that mesosomal bactoprenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1972
1972
1993
1993

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Recently, freezeetching has also been used successfully to reveal the same regularly ordered array of the cell wall in some gram-positive bacteria [10,23]. Although the ultrastructure of some lactobacilli was extensively studied by electron microscopy of thin sections [3,12,27], little is known of the freeze-etched structure of the organisms. Higgins et al [9] demonstrated in freeze-fractured cells of Lactobacillus acidophilus that the cell wall ap peared to be a homogeneous layer with a fairly smooth outer surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, freezeetching has also been used successfully to reveal the same regularly ordered array of the cell wall in some gram-positive bacteria [10,23]. Although the ultrastructure of some lactobacilli was extensively studied by electron microscopy of thin sections [3,12,27], little is known of the freeze-etched structure of the organisms. Higgins et al [9] demonstrated in freeze-fractured cells of Lactobacillus acidophilus that the cell wall ap peared to be a homogeneous layer with a fairly smooth outer surface.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators demonstrated both vesicular and lamellar mesosomes in freeze etched gram-positive bacteria [10,16,17]. The mesosome of lactobacilli was found in thin sections [3,12,27]. Figure 4 shows an oblique-fractured face of the cytoplasm.…”
Section: Freeze-etched Cellsmentioning
confidence: 99%
“…Recent studies by Frehel et al (118) demonstrate that deposits of tellurite, which are reliable cytological indicators of respiratory activity, are scattered over the plasma membrane but never occur on the mesosomes. Moreover, isolated mesosomes are deficient in NADH oxidase, succinic dehydrogenase, AT-Pase, and cytochromes (94,107,312,365,366). The evidence that mesosomes are involved in cell division, circumstantial as it is, carries more conviction.…”
Section: Structural Basismentioning
confidence: 99%
“…There have been two biochemical findings by which involvement of the mesosomes in peptidoglycan synthesis is taken into account; (i) mesosomes contain bactoprenol, an intermediate carrier in peptidoglycan synthesis, in Lactobacillus casei and L. plantarum (39), and (ii) mesosomes have higher autolytic activity than cytoplasmic membranes in M. luteus (28). PBPs function in the synthesis and organization of peptidoglycan during cell growth and division (37).…”
Section: Discussionmentioning
confidence: 99%